Fevipiprant, an oral prostaglandin DP2 receptor (CRTh2) antagonist, in allergic asthma uncontrolled on low-dose inhaled corticosteroids. Issue 2 (24th August 2017) - Bateman, Eric D.; Guerreros, Alfredo G.; Brockhaus, Florian; Holzhauer, Björn; Pethe, Abhijit; Kay, Richard A.; Townley, Robert G.
Dose-related efficacy and safety of fevipiprant (QAW039), an oral DP2 (CRTh2) receptor antagonist, was assessed in patients with allergic asthma uncontrolled by low-dose inhaled corticosteroids (ICS). Adult patients were randomised to 12 weeks' treatment with once-daily (1, 3, 10, 30, 50, 75, 150, 300 or 450 mg q.d .) or twice-daily (2, 25, 75 or 150 mg b.i.d .) fevipiprant (n=782), montelukast 10 mg q.d . (n=139) or placebo (n=137). All patients received inhaled budesonide 200 μg b.i.d . Fevipiprant produced a statistically significant improvement in the primary end-point of change in pre-dose forced expiratory volume in 1 s at week 12 (p=0.0035) with a maximum model-averaged difference to placebo of 0.112 L. The most favourable pairwise comparisons to placebo were for the fevipiprant 150 mg q.d . and 75 mg b.i.d . groups, with no clinically meaningful differences between q.d . and b.i.d . Montelukast also demonstrated a significant improvement in this end-point. No impact on other efficacy end-points was observed. Adverse events were generally mild/moderate in severity, and were evenly distributed across doses and treatments. Fevipiprant appears to be efficacious and well-tolerated in this patient population, with an optimum total daily dose of 150 mg. Further investigations into the clinical role of fevipiprant in suitably designed phase III clinical trials are warranted. Fevipiprant, an oral DP2 receptor antagonist, is effective (dose 150 mg q.d .) in allergic asthma uncontrolled on ICS http://ow.ly/Ns5d30dlAFd